Inflation co-movement across countries in multi-maturity term structure: An arbitrage-free approach - Shi Chen; Wolfgang Karl Härdle; Weining Wang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Inflation expectation is acknowledged to be an important indicator for policy makers and financial investors. To capture a more accurate real-time estimate of inflation expectation on the basis of financial markets, we propose an arbitrage-free model across different countries in a multi-maturity term structure, where we first estimate inflation expectation by modelling the nominal and inflation-indexed bond yields jointly for each country. The Nelson-Siegel model is popular in fitting the term structure of government bond yields, the arbitrage-free model we proposed is the extension of the arbitrage-free dynamic Nelson-Siegel model proposed by Christensen, Diebold and Rudebusch (2011). We discover that the extracted common trend for inflation expectation is an important driver for each country of interest. Moreover, the model will lead to an improved forecast in a benchmark level of inflation and will provide good implications for financial markets.
Keywords: G12; E43; E31; 330; inflation expectation dynamics; arbitrage free; yield curve modelling; inflation risk